1991
DOI: 10.1161/01.cir.84.2.828
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxygen-derived free radicals in myocardial edema and ischemia in coronary microvascular embolization.

Abstract: Background. Oxygen-derived free radicals are thought to injure the ischemic heart during coronary microvascular embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 38 publications
3
33
0
1
Order By: Relevance
“…10,11 This phenomenon seems to be due to adenosine-induced hyperemia of the myocardium surrounding the embolized microregions. 12 This interpretation is further supported by a study reporting that patients who experienced a prolonged hyperemic response after a percutaneous intervention had higher creatine phosphokinase values than patients without hyperemia. 13 Similar to those findings, we found a significant difference in cardiac enzyme levels between the patients with an optimal and suboptimal postprocedural CFVR value.…”
Section: Determinants Of Impaired Cfvr After Angioplastymentioning
confidence: 81%
“…10,11 This phenomenon seems to be due to adenosine-induced hyperemia of the myocardium surrounding the embolized microregions. 12 This interpretation is further supported by a study reporting that patients who experienced a prolonged hyperemic response after a percutaneous intervention had higher creatine phosphokinase values than patients without hyperemia. 13 Similar to those findings, we found a significant difference in cardiac enzyme levels between the patients with an optimal and suboptimal postprocedural CFVR value.…”
Section: Determinants Of Impaired Cfvr After Angioplastymentioning
confidence: 81%
“…Inflammatory mediators such as TNF-␣, free oxygen radicals, and interleukins have been shown to play a major role in contractile dysfunction in the microembolized myocardium following coronary microembolization (15,17,34), possibly indicating the role of inflammation and/or edema in its pathogenesis. Such mediators can likely more easily diffuse into the perfused myocardium from the interfacial region between perfused and nonperfused myocardium (i.e., proportional to the interface's surface area) rather than from deep within the nonperfused myocardium, which would make the effect more proportional to the volume of nonperfused myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that ME induces the release of inflammatory mediators such as interleukins-6 and -8, tumor necrosis factor (TNF)-␣, 12,13 and free oxygen radicals 14,25 from the ischemic myocardium into the surrounding, nonischemic myocardium. For example, Thielmann et al 11 showed in a dog model that intracoronary infusion of exogenous TNF-␣ induced contractile dysfunction even in the absence of ME.…”
Section: Malyar Et Al Nonperfused Myocardium-to-effect Relation 1949mentioning
confidence: 99%
“…8 -10 Inflammatory cytokines have been shown to depress myocardial function 11 ; hence, it is likely that MEinduced generation of proinflammatory cytokines plays a role in myocardial contractile dysfunction after ME. [12][13][14] It seems evident that such humoral agents can readily diffuse from the surface zone of small, ischemic volumes (ie, "microperfusion defects") into nearby normal tissue, whereas this diffusion is decreasingly likely from tissue deeper within the individual ischemic volumes. Therefore, we hypothesized that in ME, the total surface area (SA) rather than the volume of embolized, nonperfused myocardium (NPM) predominantly determines regional and global LV dysfunction.…”
mentioning
confidence: 99%